2020
DOI: 10.1016/j.clinthera.2020.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress on Itch

Abstract: Psychological stress and ensuing modulation of the immune and nervous systems can have a significant impact on itch. Stress can exacerbate itch and vice versa, resulting in a vicious cycle that can greatly impair a patient's quality of life. This review summarizes the association between stress and itch, elucidates the mechanism by which these two phenomena influence one another, and explores treatment modalities that aim to reduce stress-induced itch. Methods: A complete search of the PubMed and Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 113 publications
0
24
0
Order By: Relevance
“…Psychological stress, anxiety, and fear can induce and increase itch sensation and exacerbate atopic dermatitis and urticarial disease severity in COVID-19 patients (Stefaniak and others 2020). Acute and chronic psychological stress can increase itch sensation through mast cell activation (Golpanian and others 2020). It is already known that mast cell–derived inflammatory mediators play an essential role in itch sensation in atopic dermatitis and urticaria, indicating mast cell involvement in COVID-19 pathogenesis.…”
Section: Sars-cov-2-associated Mast Cell Activation Cytokine Storm mentioning
confidence: 99%
“…Psychological stress, anxiety, and fear can induce and increase itch sensation and exacerbate atopic dermatitis and urticarial disease severity in COVID-19 patients (Stefaniak and others 2020). Acute and chronic psychological stress can increase itch sensation through mast cell activation (Golpanian and others 2020). It is already known that mast cell–derived inflammatory mediators play an essential role in itch sensation in atopic dermatitis and urticaria, indicating mast cell involvement in COVID-19 pathogenesis.…”
Section: Sars-cov-2-associated Mast Cell Activation Cytokine Storm mentioning
confidence: 99%
“…Stress is a complex dynamic condition where homeostasis, or the stability of an organism is altered, promoting the adaptation of the host. Stress aggravates itch [115][116][117], which proves that the brain is engaged in the final common stage of itch processing [118,119].…”
Section: Stress the Skin Microbiota And Itchmentioning
confidence: 95%
“…A recent study showed that patients with psoriasis who were exposed to videos of other individuals scratching exhibited changes in the white matter and functional connectivity of their brains (Najafi et al, 2020). Furthermore, regions of the brain that were shown to have higher connectivity in these patients included the bilateral cingulate gyri as well as the insula, regions known to be involved in the stress response (Golpanian et al, 2020).…”
Section: Psychosocial Comorbidities Of Psoriasis and Itchmentioning
confidence: 99%